Conceptualization and application of an environmental dashboard to benchmark technical aspects in photocatalytic hydrogen production. (July 2023) - Cruz, Pedro L.; Dufour, Javier; Iribarren, Diego
Abstract: There is a growing interest in direct solar-to-hydrogen conversion, for which photocatalysis is often considered a promising option. Although environmental advantages can be expected for such systems, several aspects should be considered when evaluating its environmental suitability. In this sense, while a complete life-cycle assessment of photocatalytic systems typically involves concerns linked to the low maturity of these technologies and its associated lack of data, this article proposes a novel methodological approach, in the form of a scoring dashboard, to environmentally benchmark technical aspects in photocatalytic hydrogen production. It is based on the identification and quantification of technical and environmental hotspots and thresholds for photocatalytic technologies targeted at producing green hydrogen. In order to illustrate the proposed approach, a case study with alternative process configurations is implemented in the methodological framework. Through this case study, the proposed configurations are assessed in terms of carbon footprint by focusing on three key aspects: sacrificial agent, power consumption, and direct CO2 emissions. In particular, two options for methanol as the sacrificial agent and two options for electricity as energy required for pumping and hydrogen compression are explored. The results show a relevant influence of the sacrificial agent source on the carbon footprint of the produced hydrogen, for which its bio-based origin would be key for the produced hydrogen to be deemed green. The proposed methodological approach is concluded to be a practical solution to benchmark photocatalytic hydrogen production systems, representing a straightforward way to define technical objectives and guide research efforts.